(untitled) (Global Journal of Human-Social Science, 2022)
From ancient and modern writings instructing the great landowner on how to deal with agriculture and forestry, with his servants, vassals and slaves, the question is raised as to the relationship between the organization of the great house as an agricultural production facility and the modern economy. The hypothesis to be confirmed is that it is precisely its normative approaches that can be corrective of the current economy and thus support the claims of current ecology. This hypothesis has an implication: the environment as a world of objects is constituted by the subject, that is, by the values of the individual, by the knowledge with which he interprets the world and by his relationship with his fellows, who belong to his world and with whom he interprets it. If one wants to understand the environment as an object, then one must begin with the subject. The subject, but also his house, is the microcosm that corresponds to the macrocosm of the environment.